The influence of espresso coffee on neurocognitive function in HIV-infected patients. Issue 9 (1st September 2016) - Bragança, M.; Marinho, M.; Marques, J.; Moreira, R.; Palha, A.; Marques-Teixeira, J.; Esteves, M.
ABSTRACT: The aim of our study was to evaluate the impact of coffee intake on cognitive function in persons living with HIV (PLWH). 130 PLWH with CD4 > 200 cells/mm 3, undetectable viral load, treated with HAART were included. A structured interview was applied and relevant clinical and laboratory data were assessed, including coffee intake. For neuropsychological assessment, the HIV Neurobehavioral Research Center Battery was chosen. Univariate nonparametric statistics and multivariate regression model were used. A significant association between espresso coffee use and a better cognitive function was verified in five of the eight psychometric measurements. In the multivariate analysis, after variable adjustment, linear regression analysis showed that coffee intake was a positive predictor for attention/working memory, executive functions and Global Deficit Score. Although the mechanisms behind the influence of caffeine on cognitive functioning are controversial, regular espresso coffee intake may have favourable effects on cognitive deterioration caused by HIV.